Pengaruh Harga, Kualitas Produk, Promosi terhadap Keputusan Pembelian Smartphone Xiaomi: Studi Kasus pada Followers Instagram Xiaomi - Fadillah, Mohammad Rizki; Batu, Reminta Lumban (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2023)
The rapid growth in information technology and communication has been seen. It is clear that these technological advances and communications make it easy to engage in such everyday activities as business activities, education, health, and easier to send information from place to place. The underlying need for such activities is the smartphone. In this study discusses the price had a partial influence on purchasing decisions of 35.9%. Product quality has a partial influence on purchasing decisions of 45.5%. Promotion has a partial influence on purchasing decisions of 17%. Price variables, product quality, promotion affect simultaneous purchasing decisions by 45.9%. The remaining 54.1% is explained by other variables outside the research model. Keywords: prices, product quality, promotion, purchase decisions.